The SCN5A point mutation M1875T, associated with familial atrial fibrillation, causes a gain-of-function effect of the cardiac Nav1.5 channel in atrial cardiomyocytes. (24th May 2021) - O"reilly, M; Sommerfeld, L; O"shea, C; Broadway-Stringer, S; Kabir, S; Andaleeb, S; Malinova, A; Reyat, J; Fortmueller, L; Pavlovic, D; Skryabin, BV; Holmes, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Leducq Foundation Background: The point mutation M1875T in the SCN5A gene, which encodes the pore-forming α-subunit of the cardiac voltage-gated Na+ channel Nav1.5, has been associated with familial atrial fibrillation (AF), but its effects on atrial cardiomyocyte electrophysiology is unclear. Aim: To investigate the effect of the point mutation M1875T on atrial electrophysiological parameters. Methods: In a novel heterozygous knock-in murine model (Scn5a-M1875T+/-), whole-cell patch clamp electrophysiology was used to investigate Na+ currents in left atrial (LA) cardiomyocytes isolated from hearts of young adult mice (10-16 weeks). LA microelectrode and optical mapping recordings were used to study action potential (AP) characteristics. Cardiac size and function were measured by transthoracic echocardiography. Atrial Scn5a gene and Nav1.5 protein expression were assessed by Rt-PCR and Western blot. Results: The Na+ current was increased in cardiomyocytes isolated from Scn5a-M1875T+/- LA (wildtype (WT) -22.7 ± 0.9 pA/pF (N = 14, n = 115); Scn5a-M1875T+/- -28.3 ± 1.1 pA/pF (N = 15, n = 117)). Scn5a-M1875T+/- intact isolated superfused LA had an elevated AP amplitude (100 ms pacing cycle length (PCL): WT 86.4 ± 0.9 mV (N = 8, n = 24); Scn5a-M1875T+/- 91.2 ± 0.7 mV (N = 8, n = 25)) and a faster peak upstroke velocity (100 ms PCL: WT 127.98 ± 3.28 mV/ms; Scn5a-M1875T+/- 142.80 ± 3.98 mV/ms). AP duration (APD) was not different apart from a small APD shortening at slow rates. Echocardiography revealed no difference in size and function at the age of investigation. Atrial Scn5a gene and Nav1.5 protein expression were comparable. When challenged with flecainide (1 µM), Scn5a-M1875T+/- LA showed less conduction slowing than WT (100 ms PCL: WT -10.43 ± 1.27 cm/s (N = 12); Scn5a-M1875T+/- -6.10 ± 1.34 cm/s (N = 12)). 5 µM flecainide caused significant increase in WT refractoriness (7/12 atria lost 1:1 capture at PCL ≤ 120 ms) compared to Scn5a-M1875T+/- (1/12). Conclusion(s): SCN5A point mutation M1875T increases the Na+ current in atrial cardiomyocytes and intact atria, leading to a faster AP upstroke and an attenuated response to flecainide.